Strategi Efektif dalam Meningkatkan Kemampuan Baca Tulis Al-Qur’an di Sekolah Dasar - Dian Muhammad; Asep Irfan Saeful Milah (Jurnal Budi Pekerti Agama Islam, 2025)
This study aims to identify and analyze effective learning strategies for improving Qur’an reading and writing skills among elementary school students. The ability to read and write the Qur’an serves as an essential foundation for students’ spiritual, moral, and cognitive development, shaping their Islamic character from an early age. This research employs a descriptive approach using a literature study method that reviews various sources, including books, journals, and previous studies related to Qur’an learning at the elementary school level. The findings indicate that a combination of several innovative strategies proves to be highly effective in enhancing Qur’an literacy skills. These strategies include the use of engaging and interactive digital learning media, the application of contextual learning approaches that connect Qur’anic teachings to students’ daily lives, and the implementation of the Problem-Based Learning model to foster critical thinking and problem-solving skills. Furthermore, strengthening students’ intrinsic motivation through a supportive and religious learning environment plays a crucial role in maintaining learning interest and discipline. The integrated implementation of these strategies not only improves students’ technical ability to read and write the Qur’an but also reinforces their character, responsibility, and spiritual awareness in the context of Islamic education at the elementary level.